Correlações dos processos de secagem e intermitência sobre a qualidade do arroz polido e integral - Martens, Samuel (2022)
Although intermittent drying is widely used in rice, the accumulative time of this process can influence the temperature of the grain mass, accentuating the thermal damage to the grains, even though the intermittence helps to minimize the fluxes of heat and humidity between the grains and the air drying. Thus, the objective of the study was to correlate the effects of drying time and intermittency of paddy rice on the physical, physicochemical and morphological quality of polished and brown rice. The experiment was carried out in a grain storage unit at farm level in the municipality of Cachoeira do Sul-RS. The batches of rice grains from mechanized harvesting, with water contents between 24 and 20% (b.u.) were immediately submitted to pre-cleaning and drying operations. The samples collected were analyzed at the Postharvest Laboratory (LAPOS) at Federal University of Santa MariaCampus Cachoeira do Sul. The treatments analyzed were drying (mean temperature of the grain mass of 49 °C), intermittence (average temperature of the grain mass of 40 °C) and the drying time of 14 hours (corresponds to the number of times the product went through the drying and intermittence processes). For each drying time, grain sampling was carried out in the drying stage and in the intermittence stage to evaluate the physical quality of paddy rice and the physicochemical and morphological quality of polished and brown rice. Among the results, it was verified that the accumulative drying time provided an increase in the temperature of the grain mass, altering the physical, physicochemical and morphological quality of the polished and brown rice. The intermittence process did not satisfactorily compensate for the number of cycles (drying time) of the grain mass in the drying chamber, in relation to the final quality of the grains, especially for polished rice.